Normalisasi Pernikahan Anak: Konstruksi Sosial pada Masyarakat Desa Karang Rejo Kabupaten Tanah Laut - Falahudin, Anisa Findia; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2024)
Child marriage is a common phenomenon in society, especially in rural communities. This research aims to analyse the social construction formed in the community that leads to the normalisation of child marriage. The research was conducted in Karang Rejo Village, Jorong Sub-district, Tanah Laut Regency. This research uses a qualitative method with a phenomenological approach. Data collection methods were observation, interview, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results showed that there is a social construction in the Karang Rejo Village community that supports the normalisation of child marriage. Social construction occurs through three processes: (1) externalisation, where individuals who marry at a child's age begin to introduce their identity in society; (2) objectification, when society forms a collective perception of child marriage; and (3) internalisation, when couples who marry at a child's age adjust to the positive or negative views that develop around them. Factors that support the normalisation of child marriage include the new culture, the old culture, and social conditions. In addition, it is also due to the belief that child marriage is considered to prevent undesirable situations in society. Based on these findings, it is hoped that the community will begin to think more wisely and consider the long-term impact of the adverse effects that will occur if this continues to be done.